Political networks and social movements : Bolivian state-society relations under Evo Morales, 2006-2016 - Valdivia Rivera, Soledad (New York : Berghahn Books, 2019)
After a landslide electoral victory in 2006, Evo Morales became the first Indigenous President of Bolivia. Morales's stunning ascent was mirrored by the rising fortunes of his political party, the leftist Movimiento al Socialismo, which today continues to challenge the status quo in Bolivian politics and implement ambitious social reforms. This study examines how the state and social movements have impacted democratization in Bolivia, along with other sectors such as NGOs and the media. Soledad Valdivia Rivera's analysis helps us to understand how the movement's relationships have come to transform the Bolivian political process as we know it.
Social movements, the state and political networks in the construction of democracy in Latin America -- Social movements in the neo-liberal state : evolution of the social movement into a political actor -- The 'state-society interface' and 'political networks' : social movements and the Bolivian constituent process, 2006-2009 -- 'Political networks' in the post-constituent period from 2010-2016 -- Political leadership and 'political networks'.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on June 12, 2019).
eBooks on EBSCOhost
Keywords: Morales Ayma, Evo, -- 1959-; Movimiento al Socialismo (Bolivia); Morales Ayma, Evo, -- 1959-; Movimiento al Socialismo (Bolivia); Political participation -- Bolivia; Democracy -- Bolivia; Social movements -- Political aspects -- Bolivia; Policy networks -- Bolivia; Bolivia -- Politics and government -- 2006-; Participation politique -- Bolivie; Mouvements sociaux -- Aspect politique -- Bolivie; Réseaux de politiques publiques -- Bolivie; Bolivie -- Politique et gouvernement -- 2006-; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; POLITICAL SCIENCE / Political Process / Political Advocacy; Democracy; Policy networks; Political participation; Politics and government; Social movements -- Political aspects; Bolivia; Since 2006